Passenger’s intention to use and loyalty towards public transport: A literature review - Son Truong Pham; Bien Van Nguyen; Anh Thi Phuong Tran; Duy Quy Nguyen-Phuoc (Tạp chí Khoa học và Công nghệ, 2023)
Public transport (PT) plays a vital role in an urban transport system since it can alleviate traffic congestion, air pollution and traffic accidents, thus promoting urban sustainability. In many countries, particularly in low- and middle-income countries, encouraging the mode shift from private vehicles to PT as well as retaining the current PT users are a challenge. One reason can be the lack of understanding about the aspects of PT services that affect the behavioural intention of users. This study reviews a growing body of peer-reviewed literature examining factors affecting the loyalty intention of PT users and factors influencing the intention to use of non-users. The methodological approach adopted to investigate these factors is also reviewed. The findings are very useful not only for authorities to develop comprehensive strategies aimed at enhancing PT ridership but also for scholars to extend key insights in this area.